Simple Liquid Nutrient Medium for Molecular Genetic Investigations of Francisella tularensis - A. A. Lapin (Проблемы особо опасных инфекций, 2009)
Proposed was the simple liquid nutrient medium for tularemia agent biomass growth with the aim to isolate DNA and antigens out of bacterial cells and to culture the tranformants of F.tularensis. Shown was that yeastrel contained complete set of amino acids and growth stimulating agents required for F.tularensis growth, except for cysteine.